PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT FEDERAL INTERNATIONAL FINANCE POS TEMPINO KABUPATEN MUARO JAMBI - Ramona Dian Saputri (Universitas Batanghari Jambi, 2019)
This study attempts to describe the implementation of the quality of service and customer satisfaction in pt.The federal international finance ( fif ) and to analyse the influence of the quality of service for customer satisfaction in pt.The federal international finance ( fif ) tempino muaro jambi. district postThe methodology used in this research is a method which is a method of diskriptif. The analytical tool in this study is simple linear regression with the aim to enter the researched data into a regression equation. The results showed that Service Quality had a significant effect on Service Satisfaction at PT. Federal International Finance (FIF), Tempino Post, Muaro Jambi Regency, which was marked by Testing the independent variable (Service Quality), from the results of the t test, the tcount < t table (5.867> 1.660), it can be concluded that Service Quality has a significant effect on Customer Satisfaction. Ho is rejected and Ha is accepted.